2011
DOI: 10.1016/j.clim.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hnrph3 as an autoantigen for acute anterior uveitis

Abstract: Acute anterior uveitis (AAU) is the most common form of autoimmune uveitis in the eye with few known autoantigens. Identification of autoantigens will improve our understanding of the molecular mechanisms and capability for disease diagnosis. Phage display is a powerful technology for autoantigen identification. However, because of uncontrollable reading frames, phage display with conventional cDNA libraries identifies high percentage of non-open reading frames (non-ORFs) with minimal implications for autoanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Such pre-panning ORF selection minimizes the interference of non-ORF clones and improves the efficiency of ORF phage selection. During multi-round phage selection, however, non-ORF clones displaying unnatural short peptides with high activities may re-emerge but can be conveniently re-eliminated by post-panning ORF selection [24]. Enriched phages after the post-panning selection should have a high percentage of ORF clones that encode real endogenous proteins with specific binding or functional activities.…”
Section: Description Of Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such pre-panning ORF selection minimizes the interference of non-ORF clones and improves the efficiency of ORF phage selection. During multi-round phage selection, however, non-ORF clones displaying unnatural short peptides with high activities may re-emerge but can be conveniently re-eliminated by post-panning ORF selection [24]. Enriched phages after the post-panning selection should have a high percentage of ORF clones that encode real endogenous proteins with specific binding or functional activities.…”
Section: Description Of Methodsmentioning
confidence: 99%
“…Our experience indicated that stringent post-panning ORF selection is important to ORF phage display, particularly with antibody bait [24]. If necessary, multi-round post-panning ORF selection may be performed to ensure a high percentage of ORF clones.…”
Section: Description Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of identifying a preferential autoantigen, a recent study involving 31 patients with acute anterior uveitis (24 with HLA-B27) and 13 healthy subjects used purified patients' IgG on a phage amplification system and further demonstrated its preferential binding to maltose-binding protein-Hnrph3 fusion protein (MBP-Hnrph3). The phage display method used in this study seems to be a valuable approach for identification of novel autoantigens like type 1 collagen α2 antigen [46].…”
Section: Identification and Localization Of The Autoantigen(s)mentioning
confidence: 99%
“…It has typically been used for antigen discovery [71]. For example, T7 cDNA display of sea snake venom gland mRNA identified rabbit anti-sea snake venom IgGs as well as new toxins [72].…”
Section: Proteomic Phage Displaymentioning
confidence: 99%